Abscisic Acid Receptors and Coreceptors Modulate Plant Water Use Efficiency and Water Productivity. Issue 2 (18th March 2019) - Yang, Zhenyu; Liu, Jinghui; Poree, Fabien; Schaeufele, Rudi; Helmke, Hendrik; Frackenpohl, Jens; Lehr, Stefan; von Koskull-Döring, Pascal; Christmann, Alexander; Schnyder, Hans; Schmidhalter, Urs; Grill, Erwin
Abstract : Abscisic acid signaling can be exploited for generating plants with improved water use efficiency, resilient to water availability and light intensity but sensitive to heat. Abstract: Improving the water use efficiency (WUE) of crop plants without trade-offs in growth and yield is considered a utopic goal. However, recent studies on model plants show that partial restriction of transpiration can occur without a reduction in CO2 uptake and photosynthesis. In this study, we analyzed the potentials and constraints of improving WUE in Arabidopsis ( Arabidopsis thaliana ) and in wheat ( Triticum aestivum ). We show that the analyzed Arabidopsis wild-type plants consume more water than is required for unrestricted growth. WUE was enhanced without a growth penalty by modulating abscisic acid (ABA) responses either by using overexpression of specific ABA receptors or deficiency of ABA coreceptors. Hence, the plants showed higher water productivity compared with the wild-type plants; that is, equal growth with less water. The high WUE trait was resilient to changes in light intensity and water availability, but it was sensitive to the ambient temperature. ABA application to plants generated a partial phenocopy of the water-productivity trait. ABA application, however, was never as effective as genetic modification in enhancing water productivity, probably because ABA indiscriminately targets all ABA receptors. ABA agonists selective for individual ABA receptors might offer an approach to phenocopy the water-productivity trait of the high WUE lines. ABA application to wheat grown under near-field conditions improved WUE without detectable growth trade-offs. Wheat yields are heavily impacted by water deficit, and our identification of this crop as a promising target for WUE improvement may help contribute to greater food security.